Experiencias de control de mujeres jóvenes en relaciones de noviazgo (2020)
The main objective of this research was to explore the experiences of young women who are controlled in the context of their dating relationships. The research design was qualitative with a transcendental phenomenological approach. Twelve women (between 19 and 23 years old) participated, all of them were involved in dating relationships characterized by control. An intentional and convenience sampling was carried out through posts published in Facebook groups from Universidad de Los Andes in Bogotá, Colombia. For data collection, individual semi-structured interviews were conducted, and the information was analyzed through latent inductive Thematic Analysis. The results indicate that controlling dating relationships show problems related to instability, codependency and one-sidedness. Findings show the possible factors explaining the emergence of control. Seven control tactics used against women in their dating relationships were identified: (1) isolation, (2) monitoring and surveillance, (3) manifestations of women as men's property, (4) manipulation, (5) humiliation, (6) attempts for changing...